2006
DOI: 10.1113/jphysiol.2006.113043
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of morphology and membrane resistance to integration of fast synaptic signals in two thalamic cell types

Abstract: PO Box 1103 Blindern, N-0317, Oslo, Norway. Email: m.c.perreault@basalmed.uio.no The lateral geniculate nucleus (LGN) of the thalamus processes visual information using two main cell types; the excitatory thalamocortical cells (TCs) and the local inhibitory interneurons (INs). Interactions between morphology and membrane properties (passive and active) determine how these neurons integrate synaptic information.As TCs and INs have strikingly different morphology and because the TCs have much lower somatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
(85 reference statements)
1
18
0
Order By: Relevance
“…This is similar to procedures used in several investigations of single neurons in other systems (e.g. Spruston & Johnston, 1992; Briska et al 2003; Perreault & Raastad, 2006). In general, there are two ways in which unblocked, voltage‐gated conductances could influence the estimates.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is similar to procedures used in several investigations of single neurons in other systems (e.g. Spruston & Johnston, 1992; Briska et al 2003; Perreault & Raastad, 2006). In general, there are two ways in which unblocked, voltage‐gated conductances could influence the estimates.…”
Section: Discussionmentioning
confidence: 79%
“…An important point concerns the problems introduced by including an incorrect value for R s in the subsequent computer modelling. In the ideal case, computer modelling would require either full compensation or independent knowledge of R s , as even relatively small errors in R s can lead to large errors in the estimates for R i (Perreault & Raastad, 2006). In a previous study we found that accurate estimation of R s in whole‐cell recordings at the axon terminal is non‐trivial (Oltedal et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous models focus on aspects of passive signal propagation in INs [33][35]. To our knowledge, the only currently available model that includes a variety of the active mechanisms in INs was primarily developed in order to study the mechanisms behind the rebound bursts [36], whereas other properties such as dendritic conductances and the relationship between somatic current injections and action potentials frequency (hereby referred to as the I/O curve) were not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Given the diverse roles of the interneuron dendrites, we expect that active dendritic conductances will be crucial for understanding the function of the LGN interneurons. By including dendritic ion-channels, we will go beyond previous modelling efforts, which typically use the simplification that the dendrites are passive (Zhu et al, 1999;Briska et al, 2003;Perreault & Raastad, 2006). The presence and kinetics of specific ion-channels will be deduced partly from previous literature (Zhu et al, 1999;Zhu & Heggelund, 2001;Acuna-Goycolea et al, 2007), and partly from our new experiments, including whole-cell voltage-clamp, and calcium imaging.…”
Section: Introductionmentioning
confidence: 99%